Analysis of the doctor-patient communication if breast cancer is diagnosed - Pacian, Anna; Kulik, Teresa Bernadetta; Pacian, Jolanta; Goniewicz, Mariusz; Kowalska, Agnieszka J. (Acta Bioethica, 2014)
The aim of the paper is the recognition and evaluation of demand for medical information among patients suffering from breast cancer. The research was conducted among 120 women with diagnosed breast cancer in the Oncological Surgery Clinic of the Independent Public Research Hospital Nº 1 in Lublin, the Oncological Clinic of the Independent Public Research Hospital Nº 1 in Lublin and the Rehabilitation Centre with the Rehabilitation Clinic at the Lublin Oncology Centre. The research included women from the Club of Women after Mastectomy “Amazons”, the Club “Amazons” at the Complex of Specialist Clinics in Ostrowiec Świętokrzyski and the Club “Amazons” in Radom. Research showed that the demand for medical information among women with diagnosed breast cancer is very high. Respondents want to know all the information concerning the diagnosis, treatment and prognosis (93%). They also expect that the doctor will give them medical information concerning further consequences of cancer and its influence on future health and life (78%). Most of the respondents expect to receive information concerning medicaments which should be taken (77%) and the essence of the conducted treatment (93%). The research analysis showed that women with diagnosed breast cancer expect that the doctor will give them reliable and real medical information. Patients want the doctor to present them the probable course of the cancer (85%) and all the possible side effects connected with it (89%).